Penyelesaian Kasus Bank Century Dalam Perspektif Hukum Perdata - Bangun Patrianto (Jurnal Hukum Dan Keadilan, 2010)
Inc.Ltd (PT) Century Bank is bank institution whose function to collect social fund and distribute again to social in the form of credit so by having social trust to the bank is main factor in its persistence. Government action and the Decision of public administration in Bill Out toward PT Century Bank is legal or even government action against the law so it is criminal law or its policy is juridical flaws.